1893 R.I. Pub. Laws 231, ch. 1180, § 1 - (:unkn) unknown (General Publisher, 1893)
Prohibited the carrying of any dirk, Bowie knife, butcher knife, dagger, razor, sword cane, air-gun, billy, metal knuckles, slungshot, pistol, or firearm of any description concealed upon his person.
--
Keywords: CARRY - CONCEALED